Anticancer Gold(III) Compounds With Porphyrin or N-heterocyclic Carbene Ligands - Tong, Ka-Chung; Hu, Di; Wan, Pui-Ki; Lok, Chun-Nam; Che, Chi-Ming (Frontiers in Chemistry, 2020)
The use of gold in medicine has a long history with recent clinical application as antiinflammatory agents for the treatment of rheumatoid arthritis (chrysotherapy), and is currently developed as potential anticancer chemotherapeutics. Gold(III) being isoelectronic to platinum(II) as in cisplatin is of great interest but it is inherently unstable and redox-reactive under physiological conditions. Coordination ligands containing C and/or N donor atom(s) such as porphyrin, pincer-type cyclometalated and/or N-heterocyclic carbene (NHC) can be employed to stabilize gold(III) ion for the preparation of anticancer active compounds. In this review, we described our recent work on the anticancer properties of gold(III) compounds and the identification of molecular targets involved in the mechanisms of action. We also summarized the chemical formulation strategies that have been adopted for the delivery of the cytotoxic gold compounds, and for ameliorating the in vivo toxicity.